Challenges nurses experienced in caring for patients with COVID-19 admitted to the Intensive Care Units: A Qualitative Study - Mojtaba Rad; Masoud Fallahi-Khoshknab; Farahnaz Mohammadi- Shahboulaghi; Kian Nourozi; Hamid Reza Khankeh (Kashan University of Medical Sciences, 2023)
Background: Nurses working in intensive care units (ICU) have experienced numerous challenges while caring for patients with COVID-19.Objectives: The aim of this study was to explore ICU nurses' experiences of caring for patients with COVID-19.Methods: This research presents part of a qualitative study conducted using a grounded theory approach. Participants consisted of nurses and physicians from the selected hospitals in Sabzevar, Neishabour, and Mashhad, Iran. Data collection was performed using semi-structured in-depth interviews. Participants were enrolled via purposive sampling during 2022-2023. A total of 21 participants were interviewed. The method of Corbin and Strauss (2015) was used to analyze the data. We used Guba and Lincoln's four criteria of credibility, dependability, transferability, and confirmability to ensure data trustworthiness.Results: Four main categories emerged from the data that collectively reflect the experiences of Iranian ICU nurses in caring for COVID-19 patients. These categories included ward overcrowding, changing patterns, complexity of care, and feeling exhausted. All of these categories show that Iranian ICU nurses were under intense pressure during the COVID-19 pandemic.Conclusion: This study showed that taking care of patients was very exhausting for nurses during the COVID-19 pandemic. Hospital authorities and nursing administrators have a responsibility to support nurses and provide them facilities to feel less stress and uncertainty, while caring for patients with COVID-19.